Predictors and a prediction model for positive fine needle aspiration biopsy in C-TIRADS 4 thyroid nodules - Yang, Zhijie; Gao, Xin; Yang, Lu (Frontiers in Endocrinology, 2023)
Objectives: To screen out the predictors and establish a prediction model of positive fine needle aspiration biopsy (FNAB) in the Chinese Guidelines for Malignant Risk Stratification of Thyroid Nodule Ultrasound (C-TIRADS) 4 thyroid nodules, and this nomogram can help clinicians evaluate the risk of positive FNAB and determine if FNAB is necessary. Methods: We retrospectively analyzed data from 547 patients who had C-TIRADS 4 thyroid nodules and underwent fine-needle aspiration biopsy (FNAB) at the Second